2015
DOI: 10.1186/s12889-015-2049-y
|View full text |Cite
|
Sign up to set email alerts
|

Active Smarter Kids (ASK): Rationale and design of a cluster-randomized controlled trial investigating the effects of daily physical activity on children’s academic performance and risk factors for non-communicable diseases

Abstract: BackgroundEvidence is emerging from school-based studies that physical activity might favorably affect children’s academic performance. However, there is a need for high-quality studies to support this. Therefore, the main objective of the Active Smarter Kids (ASK) study is to investigate the effect of daily physical activity on children’s academic performance. Because of the complexity of the relation between physical activity and academic performance it is important to identify mediating and moderating varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 53 publications
0
91
0
9
Order By: Relevance
“…We have so far contacted the authors twice. NCT02043626 and NCT02122224 are completed studies identified through a trial register, but the results have not yet been published. Based on the information provided in the trial registers, we are not able to determine the eligibility of the studies, namely, whether data for children with obesity or overweight would be available.…”
Section: Resultsmentioning
confidence: 99%
“…We have so far contacted the authors twice. NCT02043626 and NCT02122224 are completed studies identified through a trial register, but the results have not yet been published. Based on the information provided in the trial registers, we are not able to determine the eligibility of the studies, namely, whether data for children with obesity or overweight would be available.…”
Section: Resultsmentioning
confidence: 99%
“…Although guidelines specify the minimum daily level of PA for children, there is a knowledge gap about the type of physical activities school children prefer, along with factors that might predict children's PA preferences. Thus, the aim of this study was to investigate children's PA preferences using baseline data from the ASK study , which included a large sample of 10‐year‐old children from 57 elementary schools in Western Norway.…”
Section: Discussionmentioning
confidence: 99%
“…This study presents baseline data from the Active Smarter Kids (ASK) study. Detailed descriptions of the ASK study have previously been published and this study provides a brief overview of the relevant procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline data were obtained from the Active Smarter Kids (ASK) Study, a study that have previously been presented in detail . A total of 1129 (588 boys and 541 girls) 10‐year‐old healthy prepubertal children were included.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline data were obtained from the Active Smarter Kids (ASK) Study, a study that have previously been presented in detail. 18 A total of 1129 (588 boys and 541 girls) 10-year-old healthy prepubertal children were included. Before any testing was performed, written informed consent was obtained from each child's parents or legal guardians after they were given a detailed oral and written explanation of the study.…”
Section: Setting and Participantsmentioning
confidence: 99%